Pharmacological Modulation of Three Modalities of CA1 Hippocampal Long-Term Potentiation in the Ts65Dn Mouse Model of Down Syndrome - Jonah J. Scott-McKean; Adriano L. Roque; Krystyna Surewicz; Mark W. Johnson; Witold K. Surewicz; Alberto C. S. Costa (Neural Plasticity)
The Ts65Dn mouse is the most studied animal model of Down syndrome. Past research has shown a significant reduction in CA1 hippocampal long-term potentiation (LTP) induced by theta-burst stimulation (TBS), but not in LTP induced by high-frequency stimulation (HFS), in slices from Ts65Dn mice compared with euploid mouse-derived slices. Additionally, therapeutically relevant doses of the drug memantine were shown to rescue learning and memory deficits in Ts65Dn mice. Here, we observed that 1 μM memantine had no detectable effect on HFS-induced LTP in either Ts65Dn- or control-derived slices, but it rescued TBS-induced LTP in Ts65Dn-derived slices to control euploid levels. Then, we assessed LTP induced by four HFS (4xHFS) and found that this form of LTP was significantly depressed in Ts65Dn slices when compared with LTP in euploid control slices. Memantine, however, did not rescue this phenotype. Because 4xHFS-induced LTP had not yet been characterized in Ts65Dn mice, we also investigated the effects of picrotoxin, amyloid beta oligomers, and soluble recombinant human prion protein (rPrP) on this form of LTP. Whereas ≥10 μM picrotoxin increased LTP to control levels, it also caused seizure-like oscillations. Neither amyloid beta oligomers nor rPrP had any effect on 4xHFS-induced LTP in Ts65Dn-derived slices.